Strategy to Increase Sales Volume Through Marketing Mix in Los Lhokseumawe Market - Putra, Hendrawan Syah; Harahap, Ainul Yusna; Ibrahim, Siti Sara (Journal of Management and Business Innovations, 2024)
This research aims to determine the strategy for increasing sales volume through the marketing mix at the Los Market in Lhokseumawe city. This type of research is descriptive qualitative. The results of the research show that the products sold at Los Market are not yet diverse, mostly women's and children's clothing, the prices offered are relatively the same for the same products, the location of Los Market is very strategic, located in the center of Lhokseumawe city, sales promotions have not been optimally carried out by Los Market regarding the sales activities of its products, the buying and selling process takes place face to face at Los Market, the employees who work are workers who specialize in selling clothes according to the products being sold, the shop layout is not much different from one shop to another. The strategy that is expected to increase sales volume is to offer more diverse products at lower prices and carry out more intensive promotions to attract buyers' interest. The buying and selling process should also be done online by utilizing skilled employees and displaying the uniqueness of the shop selling the products. Keywords: Increase Sales Volume, Marketing Mix, Strategy